2011
DOI: 10.1260/1369-4332.14.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Retrofit of Non-Ductile RC Frames with Precast Concrete (PC) Wall Panels

Abstract: An economic, structurally effective and practically applicable strengthening method had been developed for reinforced concrete (RC) framed buildings. This study presents the test results on strengthening of deficient RC frames by using high strength precast concrete (PC) panels. The idea of the method is to convert the existing hollow brick infill wall into a load carrying system by bonding PC panels on to the plastered hollow brick infills. For this purpose, six (two reference and four strengthened) one-third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…In previous studies (Baran et al, 2010;Baran and Tankut, 2011a;2011b), plates were bonded on to the mortar coated hollow brick infill walls using an effective but at the same time an expensive import material. Although the tile adhesive for bonding of plates showed unspectacular bonding performance as compared to this material, it will obviously make the technique more economical which is one of the most important criterion in application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies (Baran et al, 2010;Baran and Tankut, 2011a;2011b), plates were bonded on to the mortar coated hollow brick infill walls using an effective but at the same time an expensive import material. Although the tile adhesive for bonding of plates showed unspectacular bonding performance as compared to this material, it will obviously make the technique more economical which is one of the most important criterion in application.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on strengthening of masonry infilled walls with carbon fiber reinforced polymer (CFRP) (Antoniades et al, 2005;Erdem et al, 2006;Binici and Özcebe, 2006;Altın et al, 2008), shotcrete with mesh reinforcement (Kahn, 1984;Alcocer et al, 1996;Acun and Sucuoğlu, 2005;Korkmaz et al, 2010), steel plates (Taghdi et al, 2000a;2000b;Farooq et al, 2006), steel fiber reinforced mortar (Sevil et al, 2011) and prefabricated panel infills (Frosch et al, 1996a;1996b;Frosch, 1996;1999;Baran and Tankut, 2011a;2011b) can be found. In addition, innovative materials such as textiles (Papanicolaou et al, 2011), ferrocement (Topçu et al, 2005;Amanat et al, 2007), epoxy and mortar injection (ElGawady et al, 2004) have also been used in strengthening of the hollow brick infill walls.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large number of existing masonry-infilled RC frames, which were designed and built according to out-of-date codes, are still in service in potential earthquake regions across the world. These RC frames are commonly referred to as substandard or nonductile frames (Baran and Tankut, 2011; Ozcelik et al, 2011; Wang et al, 2016; Zou et al, 2007). The masonry infills of these frames are generally poorly connected to the bounding frames and thus face at high risk of collapse under the future strong earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Birçok araştırmacı yapı davranışı üzerinde olumlu katkıları bulunan sıvanmış tuğla dolgu duvarları değişik yöntem ve çeşitli malzemeler kullanarak güçlendirmişlerdir. Bu yöntemler arasında karbon lifli polimer kumaş [9][10], hasır donatılı püskürtme beton [11], çelik lifli sıva [12], çelik şeritlerle [13] ve önüretimli yüksek dayanımlı betonarme panellerle [14,15] güçlendirme sayılabilir. Bu yöntemlere ek olarak güçlendirme malzemesi olarak çeşitli tekstiller kullanarak [16], ferrocement kullanarak [17], epoksi ve harç enjeksiyonu kullanarak yapılan diğer güçlendirme yöntemleri [18] sayılabilir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Betonarme panellerin kullanıldığı yöntemde BA dolgu duvar seviyesinde performans artışı elde edilmiştir. Bu çalışmada, daha önce gerçekleştirilmiş çalışmalarda [14,15] kullanılan önüretimli yüksek dayanımlı BA paneller yerine yerinde dökme normal dayanımlı beton paneller kullanarak ve bunları ithal ve pahalı olan epoksi bazlı yapıştırıcı (Sikadur 31 [19]) ile değil de ucuz ve piyasada bolca bulunan yerli üretim fayans yapıştırıcısı (KALEKİM [20] Enerji dağıtma kapasitesi bir yapının kuvvetli yer hareketlerine karşı direnç gösterebilmesinin ve davranıştaki olası iyileşmenin bir göstergesidir. Tüm elemanlar için bu değer, yatay yük-ötelenme grafiklerindeki tüm çevrimlerin alanlarının toplanması ile elde edilmiştir.…”
Section: Gi̇ri̇ş (Introduction)unclassified